Factors influencing rice production in the south-eastern belt of Ghana. Issue 12 (December 2022) - Bissah, Matilda N.; Kotey, Daniel Ashie; Tongoona, Pangirayi; Egbadzor, Kenneth Fafa; Gracen, Vern; Danquah, Eric Y.
Abstract: Ghana has great potential to produce rice for local consumption, however, the average rice produced barely meets half of the country's consumption needs. Focus group discussions (FGDs) and surveys were held within the coastal lowland rice production belt in Ghana. The FGDs were held at Okyereko and Afife followed by surveys in the two communities in addition to Dawenya and Ashaiman. The objectives were to assess the production challenges faced by farmers in the four communities and determine the rice traits preferred by the farmers. Twenty farmers were involved in each of the FGDs while 227 respondents were selected through convenient sampling for the interviews. Sixty-nine percent of respondent farmers were male, 53% were above 50 years while 44% had varied levels of education. Farmers preferences mainly related to marketable traits such as aroma (87%), taste (83%) and yield potential (78%). There was special preference for Jasmine 85 (62.8%) and Togo Marshal l (25%), an indication of the high adoption of aromatic rice varieties in the study areas. Challenges such as securing credit, input supplies, soil salinity and ageing work force were matters of grave concern to respondent farmers. Given the importance of rice cultivation in the study areas to Ghana's quest to achieve self-sufficiency in rice, targeted and coordinated support from relevant governmental and non-governmental organizations is needed to sustain a higher level of production in the study areas. Highlights: Farmers had the perception that soil salinity reduces the yield of rice. The lack of requisite machinery negatively affects rice production in Ghana. Farmers adopted flooding to reduce soil salinity stress in their rice fields. The trait most preferred by rice farmers in the study communities was aroma. Abstract : Convenient sampling; Jasmine 85; Lowland; Marketable traits; Soil salinity.